Implementasi Strategi Social Media Marketing Dan Marketing Mix 4P Pada Umkm Dapur Yura Di Desa Baturiti Terhadap Kinerja Penjualan - Yusuf Stefanus; Ngurah Gede Dwi Mahadipta; Putu Yogi Agustia Pratama; Nukke Sylvia (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
MSMEs are Micro, Small and Medium Enterprises. According to the law, MSMEs are divided into several parts, namely Micro Enterprises, Small Enterprises and Medium Enterprises. MSMEs have an important role in the Indonesian economy. As an MSME actor, of course, he hopes that MSMEs can run stably and can achieve good profits. To maintain the stability of MSMEs and achieve profits, the right Marketing Strategy is needed with the aim of increasing sales performance and increasing brand awareness. In today's digital era, Marketing Strategies that can be applied include Social Media Marketing and the 4P Marketing Mix. With the use of the right Marketing Strategy, MSME players can achieve Sales Targets. Based on these problems, the purpose of this Experimental Research is to increase knowledge and understanding of the importance of the right Marketing Strategy to Improve Sales Performance, and with this Experimental Research, researchers can compare the success rate of an MSME that uses the Right Marketing Strategy with MSMEs that do not use the Right Marketing Strategy.